Inovasi Kue Talam dengan Tepung Almond - Astiana, Rachmat; Maha Tiarani, Deswina (JURNAL MANAJEMEN KULINER, 2024)
The background of this research is the innovation of modified talam products using almond flour. In the culinary world, product innovation is a factor supporting the progress of a culinary product so that it follows its target market. With product innovation, new products can be created that can attract new consumers and meet consumer needs. In this study, the authors will compare the use of almond flour in platters in 4 types, namely 100, 75, and 50 of almond flour in talam. The research method that the writer uses is descriptive qualitative, where the writer will write down the facts that are appropriate when the writer is conducting the research and the technique of collecting data is done by means of observation, interviews and literature studies. The author identifies the problems into 3 main points of discussion, namely the influence of aroma, taste, shape and texture of the product. Second, consumer acceptance and third, the right formulation. This research was conducted by the author through the author's house and the location of the panelists when the author met. In the results of the temporary research that the author got, the use of almond flour in the talam gives a unique taste to the talam. Research will continue to be carried out by the author until all the required data has been collected.